KAJIAN PEMIKIRAN ERIK ERIKSON TENTANG PERKEMBANGAN RELIGIUS ANAK USIA KANAK-KANAK - Husaini, Husaini (Universitas Islam Negeri Sumatera Utara Medan, 2023)
This study aims to explore Erik H. Erikson’s ideas on the psychosocial development of children and their relevance to religious growth. Erikson’s theory, which highlights eight stages of human development particularly early childhood suggests that children’s religious experiences are closely linked to the formation of trust, autonomy, and initiative. This research employs a qualitative approach through a literature study. The findings indicate that children’s religious development cannot be separated from their psychosocial dynamics, emphasizing the vital role of parents and the surrounding environment in nurturing religious values.